The study of the radial location of quasi-coherent modes by heavy ion beam probe in the TJ-II stellarator - Khabanov, Ph.O.; Eliseev, L.G.; Khartchev, N.K.; Hidalgo, C.; Kozachek, A.S.; Krupnik, L.I.; Lysenko, S.E.; Melnikov, A.V.; Chmyga, A.A.; Deshko, G.N.; Khrebtov, S.M.; Komarov, A.D.; et al. (Вопросы атомной науки и техники, 2018)
Recent experiments in low magnetic shear flexible heliac TJ-II have shown that steady frequency and chirping Alfvén Eigenmodes take place with 100 kHz< fAE <300 kHz at both pure NBI and combined ECR and NBI heated plasmas with low line-averaged density ne = (0.3…1.5)×10¹⁹ m⁻³ at Low Field Side (LFS) and High Field Side (HFS) of the plasma column. Furthermore, several types of low-frequency modes with f < 30 kHz, such as suprathermal electrostatic modes, tearing-like modes, quasicoherent modes with long-range potential correlations, were also observed. Power spectra for electrostatic and electromagnetic oscillations for all types of modes are presented along with their spatial location detected by dual Heavy Ion Beam Probe (HIBP).